PENGARUH FILM PENDEK DALAM LAYANAN INFORMASI UNTUK MENINGKATKAN PERILAKU DISIPLIN SISWA DI SMP N 19 KOTA JAMBI - Muhammad, Shafari Apri; Rasimin, Rasimin; Yaksa, Rully Andi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The phenomenon at SMP Negeri 19 Jambi City is that there are students who lack discipline which can hinder their learning process. The aim of this research is to reveal the influence of short films in information services to improve student disciplinary behavior.This research uses a Quasi Experimental Design type or quasi-experimental research using Pretest Posttest one Group Design. The population in this study was 245 class VIII students. The sample in this study was 31 students taken using purposive sampling technique. The instruments or data collection tools used were interviews, observations and questionnaires. Data were analyzed using percentage calculations with formula C, normality test, and t- test.The results of this research show that the disciplined learning behavior for the pretest was 3997 and for the posttest it was 4664. Based on the results of the t-test calculations, the T count was 9.416. The value of Ttable is 2.045 with a Sig value. (2-tailed) 0.000 ie. It can be seen that Tcount > Ttable so that the hypothesis is stated that there is a difference between pretest and posttest (before and after treatment is given). Based on the results of the treatment, it was stated that H₀ was rejected and Hₐ was accepted. So it can be concluded that there is a positive and significant influence of short films in information services to improve student disciplinary behavior.